Analisis Barang Milik Negara yang Idle dan Underutilized di Wilayah Provinsi Sulawesi Barat - Awaluddin Amir; Muhammad Idris; Alam Tauhid Syukur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the analysis of State Property in the form of land and buildings that are idle (abandoned) and underutilized (not utilized properly in the West Sulawesi Province). The results of the study indicate that (1) in the management of state property in the form of land and buildings, there are still problems with asset acquisition documents or asset ownership documents that are not found so that they are still obstacles when carrying out the asset certification process as a security measure, (2) there are land assets and buildings that are still problematic administratively and legally problematic which are getting worse because they are claimed by the Community, (3) the utilization and use of assets is not optimal so that the potential of large assets is not utilized optimally and seems to be idle (abandoned) and underutilized (not utilized properly) (4) buildings that are left are finally badly damaged (5) there are no rental fees for users of land and building assets, likewise there are no loan fees applied so that the potential to get income or non-tax state revenue from assets does not exist.